Understanding the health system utilisation and reasons for avoidable mortality after fatal injury within a Three-Delays framework in Karonga, Northern Malawi: a retrospective analysis of verbal autopsy data - Justine Davies; Lucia D’Ambruoso; Andy J M Leather; John Whitaker; Rory F Rickard; Albert Dube; Abena S Amoah; Idara Edem (BMJ Open, 2024)
Objectives To use verbal autopsy (VA) data to understand health system utilisation and the potential avoidability associated with fatal injury. Then to categorise any evident barriers driving avoidable delays to care within a Three-Delays framework that considers delays to seeking (Delay 1), reaching (Delay 2) or receiving (Delay 3) quality injury care.Design Retrospective analysis of existing VA data routinely collected by a demographic surveillance site.Setting Karonga Health and Demographic Surveillance Site (HDSS) population, Northern Malawi.Participants Fatally injured members of the HDSS.Primary and secondary outcome measures The primary outcome was the proportion of fatal injury deaths that were potentially avoidable. Secondary outcomes were the delay stage and corresponding barriers associated with avoidable deaths and the health system utilisation for fatal injuries within the health system.Results Of the 252 deaths due to external causes, 185 injury-related deaths were analysed. Deaths were predominantly among young males (median age 30, IQR 11–48), 71.9% (133/185). 35.1% (65/185) were assessed as potentially avoidable. Delay 1 was implicated in 30.8% (20/65) of potentially avoidable deaths, Delay 2 in 61.5% (40/65) and Delay 3 in 75.4% (49/65). Within Delay 1, ‘healthcare literacy’ was most commonly implicated barrier in 75% (15/20). Within Delay 2, ‘communication’ and ‘prehospital care’ were the most commonly implicated in 92.5% (37/40). Within Delay 3, ‘physical resources’ were most commonly implicated, 85.7% (42/49).Conclusions VA is feasible for studying pathways to care and health system responsiveness in avoidable deaths following injury and ascertaining the delays that contribute to deaths. A large proportion of injury deaths were avoidable, and we have identified several barriers as potential targets for intervention. Refining and integrating VA with other health system assessment methods is likely necessary to holistically understand an injury care health system.